Understanding Geographies of Polarization and Peripheralization Perspectives from Central and Eastern Europe and Beyond - Lang, Thilo.; Lang, Thilo.; Henn, Sebastian.; Henn, Sebastian.; Ehrlich, Kornelia.; Ehrlich, Kornelia.; Sgibnev, Wladimir.; Sgibnev, Wladimir. (New Geographies of Europe,, 2015)
This book presents a multifaceted perspective on regional development and corresponding processes of adaptation and response, focusing on the concepts of polarization and peripheralization. It discusses theoretical and empirical foundations and presents several compelling case studies from Central and Eastern Europe and beyond.